2017
DOI: 10.1111/codi.13833
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is a risk factor for pulmonary metastasis in colorectal cancer

Abstract: Smoking may be a risk factor for pulmonary metastasis of colorectal cancer. Cessation of smoking should be recommended to prevent pulmonary metastasis, although further basic and clinical studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…Previous studies reported the incidence of liver metastases, lung metastases, bone metastases, and brain metastases, which ranged from 14.5 to 26.5% [10][11][12][13], 2.4 to 6.9% [8,14], 2.7 to 10% [4,15,16], and 0.23 to 3% [4,6,7,15], respectively. Differences in the sample size of each study may have led to these inconsistent results for the same metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the incidence of liver metastases, lung metastases, bone metastases, and brain metastases, which ranged from 14.5 to 26.5% [10][11][12][13], 2.4 to 6.9% [8,14], 2.7 to 10% [4,15,16], and 0.23 to 3% [4,6,7,15], respectively. Differences in the sample size of each study may have led to these inconsistent results for the same metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results demonstrated significantly higher number of cysts in upper lobe location in current smokers compared with previous and never smokers, which may be caused by the relatively overventilation of the lung apices compared to the lung bases, which are prone to smoke-related inhalation injury [19]. Furthermore, both current as well as previous smokers revealed significantly higher numbers of pulmonary metastases compared with non-smokers and MPNST, which might be explained by the protooncogenic stimulation caused by smoking [20] and by the fact, that smoking is regarded as risk factor for pulmonary metastasis in gastrointestinal cancers [21,22] and breast cancer [23]. Moreover, it has been suggested, that NF1 may enhance the pulmonary sensitivity to cigarette smoke [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was a significant increase in the number of pulmonary metastases of CRC, as shown radiologically and pathologically, in the smoking group compared to the control group; this is consistent with the results of a previous clinical study. 9 The culprit was the trapping of cancer cells by ICAM-1, an adhesion molecule overexpressed due to inflammation caused by smoking. Collectively, smoking is a risk factor for pulmonary metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our retrospective study showed that current smokers, compared with former smokers and those who never smoked, might have a significantly increased risk of metachronous pulmonary metastasis following curative resection of CRC. 9 Although CRC is a high morbidity cancer that can have a high survival rate when diagnosed and treated early, it is known that prognosis worsens when it metastasizes to other organs. Thus, determining the relationship between smoking and pulmonary metastasis of CRC may lead to not only proof of smoking toxicity and add to the risks of passive smoking, but may also lead to the development of new drug therapies for pulmonary metastasis.…”
Section: Introductionmentioning
confidence: 99%